2014
DOI: 10.18632/oncotarget.2084
|View full text |Cite
|
Sign up to set email alerts
|

Notch signaling drives multiple myeloma induced osteoclastogenesis

Abstract: Multiple myeloma (MM) is closely associated with bone destruction. Once migrated to the bone marrow, MM cells unbalance bone formation and resorption via the recruitment and maturation of osteoclast precursors.The Notch pathway plays a key role in different types of cancer and drives several biological processes relevant in MM, including cell localization within the bone marrow, proliferation, survival and pharmacological resistance.Here we present evidences that MM can efficiently drive osteoclastogenesis by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
54
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 43 publications
6
54
0
Order By: Relevance
“…4,[53][54][55] In MM, induction of Notch in OCL through the interaction with tumor cells has been shown to represent one of the mechanisms driving osteoclastogenesis. 2,25 In agreement with these data we found that the pharmacological inhibition of Notch with RO4929097 during OCL differentiation as well as in mature OCL results in a significant reduction in OCL number and function.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…4,[53][54][55] In MM, induction of Notch in OCL through the interaction with tumor cells has been shown to represent one of the mechanisms driving osteoclastogenesis. 2,25 In agreement with these data we found that the pharmacological inhibition of Notch with RO4929097 during OCL differentiation as well as in mature OCL results in a significant reduction in OCL number and function.…”
Section: Discussionsupporting
confidence: 88%
“…25,32 Therefore, we investigated whether the inhibition of Notch with RO4929097 could affect osteoclast (OCL) differentiation and function. Peripheral blood MNC were differentiated into OCL by treatment with macrophage colony-stimulating factor (M-CSF) and receptor activator of nuclear factor-kB ligand (RANKL), with or without 1 mM RO4929097.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, it plays an important role in the cell proliferation and differentiation, organ development and diseases [19]. Previous evidence has also suggested that Notch signaling participates in the chondrogenesis and the proliferation and differentiation of chondrocytes [20,21].The Notch pathway exists in the differentitation and biological processes of multiple myeloma, including cell localization with the bone marrow, proliferation, survival and pharmachological resistance [22], Jag-1 and Notch-1 exist in mammalian cells [23], some studies have indicated that Notch signaling mediated by Jag-1 plays a role in the development of many tissues [24], and has an important effect on the chondrogenesis of BMSCs [25].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple myeloma cells can activate the North pathway due to the over-express of Jad-1 ligands [22,26] thus activate osteoclastogenesis. In T cell acute lymphoblastic luekaemia, Notch-1 can enhance the proliferative advantage and specific chemotactic abilities through acting in concert with chemokine receptor pathways, therefore influencing tumor cell progression and localization [27].…”
Section: Introductionmentioning
confidence: 99%